Functional traits, land‐use change and the structure of present and future bird communities in tropical forests. Issue 10 (14th May 2014) - Newbold, Tim; Scharlemann, Jörn P. W.; Butchart, Stuart H. M.; Şekercioğlu, Çağan H.; Joppa, Lucas; Alkemade, Rob; Purves, Drew W.
Abstract Aim Habitat loss continues to cause loss of biodiversity. To quantify the effects of land‐use change on the diversity and composition of ecological communities – in terms of functional groups – we make modelled estimates of the impact of past and future (to 2050) land‐use change on the overall diversity and dietary guild structure of tropical forest bird communities. Location Tropical and subtropical forests (40° S to 40° N). Methods Using a likelihood‐based model, we project the impact of land‐use intensity on the diversity and functional structure of tropical forest bird communities, including an estimation of uncertainty. To explore the extent to which predicted impacts are determined by the inherent sensitivity of communities because of the traits possessed by the species present, we quantify communities in terms of trait composition and explore relationships between trait composition and diversity/guild loss. Results We estimate that habitat loss has led to an average decrease of 4% in total abundance, but with marked differences across different guilds, leading to substantial changes in community composition: an 11.4% loss of frugivores, 7.8% loss of nectarivores and 7.3% loss of insectivores, and a 4.0% gain of other herbivores. Projected land‐use change is predicted to result in average future losses of 1% of total abundance, 1% of each of frugivores, nectarivores and insectivores, but no average change in the abundance of other herbivores. Past and future changes have varied substantially across the biome, owing to variation in land‐use change and in the initial trait composition of communities. Main conclusions We predict that marked changes in community structure have occurred in the past and will occur in the future, with disproportionate losses of frugivores, nectarivores and insectivores compared with other species; these species are known to provide important ecosystem services. In the past, South America has been particularly strongly affected, while Southeast Asia will experience the strongest impacts in the future.